Kejahatan Perundungan Menyebabkan Kematian Perspektif Hukum Positif dan Hukum Pidana Islam - Hermalia Putri, Shanty; Zulkarnain, Zulkarnain (Dinasti Review Publisher, 2024)
At present, there is a lot of deviant child behavior that has even led to crime. One of them is the crime of bullying, which can occur anywhere, such as at home, school, and society. This bullying crime has a negative impact on victims such as trauma, depression, physical injury and even death. This research aims to find out the forms and triggering factors of bullying crimes causing death, and to find out how the comparison of the regulation of bullying crimes causing death according to the perspective of Positive law and Islamic Criminal law. The method used is library research method with qualitative research type. And using a comparative legal approach between Positive Law and Islamic Criminal Law. The results of the study found that in Positive Law, the punishment for the crime of bullying causing death is imprisonment and fines as well as warnings, guidance, community service and job training if the perpetrator is a minor. Meanwhile, in Islamic Criminal Law, if an adult is the perpetrator of the crime of bullying causing death, the punishment can be hudud and qishash. But if the perpetrator is a minor, he is punished with ta'zir.